Preparation method of cobalt ferrite manganese ferrite L-polylactic acid composite antibacterial bone scaffold

By combining cobalt ferrate-manganese ferrate composite powder with levopolylactic acid, and using selective laser sintering and alternating magnetic field to stimulate magnetothermal effect and chemical dynamics synergistic antibacterial, the lack of levopolylactic acid bone implants in the prior art is solved. The problem of antibacterial function achieves efficient antibacterial effects and safe implants.

CN119424758APending Publication Date: 2025-02-14JIANGXI UNIV OF SCI & TECH
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411519896.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-29
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

The existing levopolylactic acid bone implants lack antibacterial function and are prone to bacterial infection. The magneto-thermal conversion efficiency of direct introduction of cobalt ferrite into the levopolylactic acid scaffold is low and the antibacterial effect is insufficient.

Method used

Cobalt ferrite-manganese ferrite composite powder combined with levo polylactic acid was used to prepare cobalt ferrite-manganese ferrite/levo polylactic acid composite antibacterial bone scaffolds through selective laser sintering technology, and the magnetothermal effect and chemical dynamic coordination were stimulated by alternating magnetic field. Antibacterial.

Benefits of technology

Under the action of alternating magnetic field, the scaffold destroys the bacterial biofilm through magnetothermal effects, promotes the reactive oxygen produced by chemical motivation to enter the bacteria and kills bacteria, significantly improves the antibacterial effect and avoids implant-related infections.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119424758A_ABST
    Figure CN119424758A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a cobalt ferrite manganese ferrite L-polylactic acid composite antibacterial bone scaffold, which comprises the following steps: growing manganese ferrite on the surface of cobalt ferrite in situ to prepare cobalt ferrite-manganese ferrite composite powder, and adding the prepared cobalt ferrite-manganese ferrite composite powder into ethanol to prepare a suspension; the preparation method comprises the following steps: preparing cobalt ferrite-manganese ferrite and poly-L-lactic acid composite powder, performing ultrasonic mixing with poly-L-lactic acid ethanol suspension, performing centrifugal drying to obtain the cobalt ferrite-manganese ferrite and poly-L-lactic acid composite powder, and finally performing selective laser sintering to obtain the cobalt ferrite-manganese ferrite / poly-L-lactic acid composite antibacterial bone scaffold. As a novel bone implant, the cobalt ferrite-manganese ferrite / poly-L-lactic acid composite antibacterial bone scaffold prepared by the invention can generate local high temperature and a large amount of active oxygen under the excitation of an alternating magnetic field, so that a good antibacterial effect is achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of additive manufacturing composite scaffolds, and specifically to a method for preparing a cobalt ferrite and manganese ferrite left-handed polylactic acid composite antibacterial bone scaffold. Background Art

[0002] Bone defects caused by trauma, tumors, osteoarthritis, etc. seriously affect human health. In recent years, artificial bone implants have been widely used in bone defect repair due to their wide sources and no immune rejection. Poly-L-lactic acid is one of the few biomedical materials approved by the U.S. Food and Drug Administration. It has good biocompatibility, processability and degradability, and is often used to prepare bone implants. However, existing poly-L-lactic acid implants lack antibacterial function. Bone implants are often accompanied by bacterial infection after transplantation, usually requiring multiple follow-up surgeries, and even leading to bone transplantation failure. Therefore, it is necessary to develop bone scaffolds with antibacterial function to destroy bacterial biofilms and kill bacteria, which is of great significance for the treatment of implant-related infections.

[0003] Chemodynamic therapy can produce reactive oxygen through Fenton or Fenton-like reactions, interfering with bacterial gene transcription and DNA replication processes, thereby killing bacteria. However, biofilms and bacterial membranes provide a natural barrier to the penetration of reactive oxygen, reducing the efficiency of chemodynamic antibacterial therapy. Magnetic hyperthermia therapy improves tissue penetration by applying an alternating magnetic field. It can precisely control local temperature in a remotely controlled manner with nanoscale spatial resolution, which can not only destroy bacterial biofilms, but also increase the permeability of cell membranes.

[0004] Cobalt ferrite is a typical hard magnetic ferrite with high magnetic anisotropy, coercive force and remanence. Introducing it into left-handed polylactic acid implants is expected to absorb magnetic energy and convert it into heat, giving the implant antibacterial properties. However, the magnetothermal conversion efficiency of cobalt ferrite is low, and high doses and long-term magnetic exposure are required to achieve a bactericidal effect, which can easily damage surrounding normal cells and tissues. Manganese ferrite is a typical soft magnetic material with high saturation magnetic susceptibility and magnetic permeability. Manganese ferrite is in situ grown on the surface of cobalt ferrite to construct soft and hard magnetic biphasic core-shell nanoparticles. Under the action of an alternating magnetic field, the interfacial exchange coupling effect between the soft and hard magnets will cause the redirection of the magnetic moment, more effectively converting the magnetic energy transfer into heat energy, thereby improving the magnetothermal conversion efficiency. In addition, the metal ions released by the composite material react with hydrogen peroxide at the infection site to generate hydroxyl radicals, achieving synergistic antibacterial effects of magnetothermal and chemical dynamics.

[0005] In the prior art, there is no research on adding cobalt ferrite-manganese ferrite composite powder into L-polylactic acid to prepare bone scaffolds to achieve antibacterial properties. Summary of the invention

[0006] In order to solve the problem that the direct introduction of cobalt ferrite into a L-polylactic acid scaffold has low magnetothermal conversion efficiency and leads to insufficient antibacterial effect, the present invention provides a method for preparing a cobalt ferrite-manganese ferrite L-polylactic acid composite antibacterial bone scaffold.

[0007] To achieve the above object, the present invention provides the following technical solution: a method for preparing a cobalt ferrite and manganese ferrite L-polylactic acid composite antibacterial bone scaffold, comprising the following steps: S1, preparing cobalt ferrite-manganese ferrite composite powder by in-situ growth of manganese ferrite on the surface of cobalt ferrite; S2, adding the prepared cobalt ferrite-manganese ferrite composite powder to ethanol to prepare a suspension, ultrasonically mixing the suspension with L-polylactic acid ethanol, and centrifugally drying to obtain a cobalt ferrite-manganese ferrite and L-polylactic acid composite powder; S3. Cobalt ferrite-manganese ferrite / L-polylactic acid composite antibacterial bone scaffold was prepared by selective laser sintering.

[0008] Preferably, in step S1, a cobalt ferrite solution is prepared to obtain a cobalt ferrite-manganese ferrite / L-polylactic acid composite antibacterial bone scaffold, and the steps are as follows: S11, dispersing cobalt ferrite in ethanol and ultrasonically treating it to prepare an ethanol solution of cobalt ferrite; then in-situ growing manganese ferrite in the prepared cobalt ferrite solution, the steps are as follows: adding ferric acetylacetonate, manganese acetylacetonate, octadecyl alcohol, oleic acid, oleylamine, and phenyl ether to the prepared cobalt ferrite solution in sequence, ultrasonically dispersing and then magnetically stirring, heating the mixed solution in a tube furnace to react; repeatedly centrifuging and washing the solution with ethanol, and drying to obtain a cobalt ferrite-manganese ferrite composite powder; S12, dispersing L-polylactic acid powder in anhydrous ethanol to obtain a L-polylactic acid suspension, and then dispersing cobalt ferrite-manganese ferrite composite powder into the L-polylactic acid suspension to obtain a cobalt ferrite-manganese ferrite / L-polylactic acid composite suspension, and obtaining a cobalt ferrite-manganese ferrite / L-polylactic acid composite powder after ultrasonication, centrifugation, drying, and grinding; S13, placing the cobalt ferrite-manganese ferrite / L-polylactic acid composite powder in a selective laser sintering system, sintering it layer by layer according to a pre-established three-dimensional model, removing the unsintered powder after sintering, and obtaining the cobalt ferrite-manganese ferrite / L-polylactic acid composite antibacterial bone scaffold.

[0009] Preferably, in step S11, the mass volume ratio of cobalt ferrite to ethanol is 1 mg:1 mL, the ultrasonic dispersion time is 30-60 min, and the temperature is 15-50°C; the magnetic stirring time is 30-60 min; the heating temperature is 300-350°C, and the heating rate is 10°C / min; the number of centrifugation is 2-4 times, the centrifugation time is 10-15 min, the centrifugal speed is 8000-10000 r / min, the drying time is 6-12 h, and the drying temperature is 50-80°C.

[0010] Preferably, in step S12, the particle size of L-polylactic acid is 10-40 um; in the cobalt ferrite-manganese ferrite / L-polylactic acid composite powder, the mass fraction of cobalt ferrite-manganese ferrite is 2-10%, and the mass fraction of L-polylactic acid is 90-98%.

[0011] Preferably, in step S13, during the laser sintering process, the laser power is 0.5-3W, the scanning speed is 100-200mm / s, the scanning interval is 0.1-0.2mm, the spot diameter is 0.5-1.5mm, the powder layer thickness corresponding to the cobalt ferrite-manganese ferrite / levorotatory polylactic acid composite powder is 0.1mm, and the corresponding powder bed preheating temperature is 100-200°C.

[0012] Preferably, in step S11, the particle size of the cobalt ferrite selected is 10-20 nm.

[0013] Preferably, in step S11, the molar ratio of iron acetylacetonate to manganese acetylacetonate is 2:1.

[0014] Preferably, in step S11, the molar ratio of octadecyl alcohol, oleic acid and oleylamine is 5:6:6.

[0015] Preferably, in step S2, the synthesized cobalt ferrite-manganese ferrite composite powder has a core-shell structure, and the shell thickness is 0.5-2 nm.

[0016] Compared with the prior art, the present invention has the following beneficial effects: In the present invention, the cobalt ferrite-manganese ferrite / levorotatory polylactic acid composite antibacterial bone scaffold is prepared by selective laser sintering, has controllable porosity, personalized three-dimensional structure, good biocompatibility, and is beneficial to the transmission of nutrients and tissue regeneration. In addition, under the excitation of the alternating magnetic field, the scaffold destroys the bacterial biofilm through the magnetothermal effect, promotes the active oxygen generated by chemical power to enter the bacteria and kill the bacteria, and avoids implant-related infection. At the same time, the degradation rate matches the bone tissue regeneration rate, and no secondary surgery is required.

[0017] The present invention controls the content of cobalt ferrite-manganese ferrite and adjusts the process parameters of the laser sintering system to prepare a cobalt ferrite-manganese ferrite / L-polylactic acid composite antibacterial bone scaffold to cope with the problem of bone implant-related infection.

[0018] The present invention prepares a cobalt ferrite-manganese ferrite / levorotatory polylactic acid composite antibacterial bone scaffold as a novel bone implant material. The cobalt ferrite-manganese ferrite / levorotatory polylactic acid composite antibacterial bone scaffold is made of cobalt ferrite-manganese ferrite / levorotatory polylactic acid composite powder based on additive manufacturing technology, wherein the left-handed polylactic acid has good biocompatibility and degradability, and the cobalt ferrite-manganese ferrite composite material can generate local high temperature and a large amount of active oxygen under the excitation of an alternating magnetic field, and exhibits excellent antibacterial effects on Escherichia coli and Staphylococcus aureus. The antibacterial rate of the prepared cobalt ferrite-manganese ferrite / levorotatory polylactic acid composite bone scaffold reaches more than 90%.

[0019] Other advantages, objectives and features of the present invention will be embodied in part through the following description, and in part will be understood by those skilled in the art through study and practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 The preparation process and characterization diagram of the cobalt ferrite-manganese ferrite / L-polylactic acid composite antibacterial bone scaffold in Example 1 of the present invention; Figure 2 Schematic diagram of the anti-biofilm test results of the cobalt ferrite-manganese ferrite / L-polylactic acid composite antibacterial bone scaffold, L-polylactic acid scaffold, and cobalt ferrite / L-polylactic acid scaffold prepared in Example 1 of the present invention; Figure 3 Schematic diagram of the antibacterial experimental results of the cobalt ferrite-manganese ferrite / L-polylactic acid composite antibacterial bone scaffold, L-polylactic acid scaffold, and cobalt ferrite / L-polylactic acid scaffold prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0021] The technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention. Example 1

[0022] This embodiment provides a method for preparing a cobalt ferrite and manganese ferrite L-polylactic acid composite antibacterial bone scaffold, comprising the following steps: Step 1, dispersing 60 mg of cobalt ferrite with a particle size of 10-20 nm in 60 ml of ethanol and ultrasonically treating for 30 minutes to prepare an ethanol solution of cobalt ferrite; then in-situ growing manganese ferrite in the prepared cobalt ferrite solution, the steps are as follows: adding 2 mmol of ferric acetylacetonate, 1 mmol of manganese acetylacetonate, 5 mmol of octadecyl alcohol, 6 mmol of oleic acid, 6 mmol of oleylamine, and 20 ml of phenyl ether to the prepared cobalt ferrite solution in sequence, ultrasonically dispersing for 30 minutes and then magnetically stirring for 1 hour, transferring the mixed solution to a tube furnace and heating it to 300° C. at a rate of 10° C. / min and maintaining it for 1 hour; repeatedly washing the solution with ethanol, the centrifugation time is 10 minutes, the centrifugation speed is 10000 r / min, and the solution after centrifugation is dried at 60° C. for 6 hours to obtain a cobalt ferrite-manganese ferrite composite powder.

[0023] Step 2: Disperse 4.75 g of left-handed polylactic acid powder in 50 ml of anhydrous ethanol and perform ultrasonic treatment for 1 h to obtain a left-handed polylactic acid suspension. Then disperse 0.25 g of cobalt ferrite-manganese ferrite composite powder into the left-handed polylactic acid suspension and perform ultrasonic treatment for 1 h to obtain a cobalt ferrite-manganese ferrite / left-handed polylactic acid composite suspension. Centrifuge for 15 min at a speed of 8000 r / min. Dry the solution at 60 ° C for 12 h to obtain a cobalt ferrite-manganese ferrite / left-handed polylactic acid composite powder.

[0024] Step 3: Place the cobalt ferrite-manganese ferrite / levorotatory polylactic acid composite powder in a selective laser sintering system with a laser power of 1 W, a scanning speed of 100 mm / s, a scanning spacing of 0.1 mm, a spot diameter of 1 mm, a powder layer thickness of 0.1 mm, and a corresponding powder bed preheating temperature of 150 ° C. Sinter layer by layer according to the pre-established three-dimensional model. After sintering, remove the unsintered powder to obtain a cobalt ferrite-manganese ferrite / levorotatory polylactic acid composite antibacterial bone scaffold.

[0025] The cobalt ferrite-manganese ferrite / L-polylactic acid composite antibacterial bone scaffold prepared in this example is applied to a new bone implant material. The preparation process and transmission electron microscopy characterization results are shown in FIG. Figure 1 As shown in the figure, it can be seen that the structure of the cobalt ferrite-manganese ferrite composite material is approximately spherical, the manganese ferrite shell is thin and evenly distributed on the surface of the cobalt ferrite core; the average pore size of the cobalt ferrite-manganese ferrite / levorotatory polylactic acid composite antibacterial bone scaffold is about 850±40um, and the porous structure is conducive to the continuous release of nanoparticles and metal ions after scaffold degradation, thereby achieving the persistence of magnetothermal and antibacterial properties.

[0026] Antibacterial experiment,The operation of the antibacterial experiment is as follows: Escherichia coli and Staphylococcus aureus are selected as experimental bacteria.

[0027] First, the inhibitory effect of scaffolds with different material components on bacterial biofilm was evaluated. The specific experimental steps were as follows: 6 Escherichia coli and Staphylococcus aureus were cultured with different scaffolds in a well plate at 37°C for 48 hours to form a dense biofilm, and then the scaffold-bacteria mixed solution was treated with an alternating magnetic field for 5 minutes. The residual biofilm was washed with PBS solution and fixed with methanol for 30 minutes, and then the biofilm was stained with 1% crystal violet for 30 minutes. The microscopic morphology of the stained biofilm was observed by fluorescence microscopy, and the macroscopic morphology was photographed with a digital camera to obtain the anti-biofilm test results of each material group. Figure 2 As shown, from Figure 2 It can be seen that the L-polylactic acid group showed a dark purple color, indicating that relatively complete biofilms were formed on the surface of Escherichia coli and Staphylococcus aureus; the cobalt ferrite / L-polylactic acid group was relatively light in color, while the cobalt ferrite-manganese ferrite / L-polylactic acid group was the lightest in color, even transparent, indicating that the cobalt ferrite-manganese ferrite / L-polylactic acid scaffold had the strongest inhibitory effect on bacterial biofilms. This is because the cobalt ferrite-manganese ferrite / L-polylactic acid group had stronger magnetothermal properties under the action of the alternating magnetic field.

[0028] In addition, the bactericidal effect of scaffolds with different material components was evaluated; the specific steps of the experiment were as follows: 6 The bacterial strains and different scaffolds were cultured in a well plate at 37°C for 12 h, and then the scaffold-bacteria mixed solution was treated with an alternating magnetic field for 5 min. The obtained bacterial solution was diluted 10 6 The diluted bacterial solution was evenly spread on the plate and placed in a 37°C solid incubator for 12 hours. The image of the agar plate colony was taken by a digital camera, and the number of colonies was calculated by counting software. The antibacterial rate was calculated according to the following formula:

[0029] The results are as follows Figure 3 As shown, from Figure 3 It can be seen that more bacterial colonies appeared in the L-polylactic acid group, the number of bacterial colonies in the cobalt ferrite / L-polylactic acid group decreased, and the inhibition rates against Escherichia coli and Staphylococcus aureus were 64.0% and 75.1%, respectively. The number of bacterial colonies in the cobalt ferrite-manganese ferrite / L-polylactic acid group was the least, and the inhibition rates against Escherichia coli and Staphylococcus aureus were 93.4% and 94.2%, respectively, showing the best antibacterial ability among all groups. Example 2

[0030] This embodiment provides a method for preparing a cobalt ferrite and manganese ferrite L-polylactic acid composite antibacterial bone scaffold, comprising the following steps: Step 1, dispersing 60 mg of cobalt ferrite with a particle size of 10-20 nm in 60 ml of ethanol and ultrasonically treating for 30 minutes to prepare an ethanol solution of cobalt ferrite; then in-situ growing manganese ferrite in the prepared cobalt ferrite solution, the steps are as follows: adding 2 mmol of ferric acetylacetonate, 1 mmol of manganese acetylacetonate, 5 mmol of octadecyl alcohol, 6 mmol of oleic acid, 6 mmol of oleylamine, and 20 ml of phenyl ether to the prepared cobalt ferrite solution in sequence, ultrasonically dispersing for 30 minutes and then magnetically stirring for 1 hour, transferring the mixed solution to a tube furnace and heating it to 300° C. at a rate of 10° C. / min and maintaining it for 1 hour; repeatedly washing the solution with ethanol, the centrifugation time is 10 minutes, the centrifugation speed is 10000 r / min, and the solution after centrifugation is dried at 60° C. for 6 hours to obtain a cobalt ferrite-manganese ferrite composite powder.

[0031] Step 2: Disperse 4.65 g of L-polylactic acid powder in 50 ml of anhydrous ethanol and perform ultrasonic treatment for 1 h to obtain a L-polylactic acid suspension. Then disperse 0.35 g of cobalt ferrite-manganese ferrite composite powder into the L-polylactic acid suspension and perform ultrasonic treatment for 1 h to obtain a cobalt ferrite-manganese ferrite / L-polylactic acid composite suspension. Centrifuge for 15 min at a speed of 8000 r / min. Dry the solution at 60 ° C for 12 h to obtain a cobalt ferrite-manganese ferrite / L-polylactic acid composite powder.

[0032] Step 3: Place the cobalt ferrite-manganese ferrite / levorotatory polylactic acid composite powder in a selective laser sintering system with a laser power of 1.5 W, a scanning speed of 120 mm / s, a scanning spacing of 0.15 mm, a spot diameter of 1 mm, a powder layer thickness of 0.1 mm, and a corresponding powder bed preheating temperature of 150 ° C. Sinter layer by layer according to the pre-established three-dimensional model. After sintering, remove the unsintered powder to obtain a cobalt ferrite-manganese ferrite / levorotatory polylactic acid composite antibacterial bone scaffold. Example 3

[0033] This embodiment provides a method for preparing a cobalt ferrite and manganese ferrite L-polylactic acid composite antibacterial bone scaffold, comprising the following steps: Step 1, dispersing 60 mg of cobalt ferrite with a particle size of 10-20 nm in 60 ml of ethanol and ultrasonically treating for 30 minutes to prepare an ethanol solution of cobalt ferrite; then in-situ growing manganese ferrite in the prepared cobalt ferrite solution, the steps are as follows: adding 2 mmol of ferric acetylacetonate, 1 mmol of manganese acetylacetonate, 5 mmol of octadecyl alcohol, 6 mmol of oleic acid, 6 mmol of oleylamine, and 20 ml of phenyl ether to the prepared cobalt ferrite solution in sequence, ultrasonically dispersing for 30 minutes and then magnetically stirring for 1 hour, transferring the mixed solution to a tube furnace and heating it to 300° C. at a rate of 10° C. / min and maintaining it for 1 hour; repeatedly washing the solution with ethanol, the centrifugation time is 10 minutes, the centrifugation speed is 10000 r / min, and the solution after centrifugation is dried at 60° C. for 6 hours to obtain a cobalt ferrite-manganese ferrite composite powder.

[0034] Step 2: Disperse 4.75 g of L-polylactic acid powder in 50 ml of anhydrous ethanol and perform ultrasonic treatment for 1 h to obtain a L-polylactic acid suspension. Then disperse 0.25 g of cobalt ferrite-manganese ferrite composite powder into the L-polylactic acid suspension and perform ultrasonic treatment for 1 h to obtain a cobalt ferrite-manganese ferrite / L-polylactic acid composite suspension. Centrifuge for 15 min at a speed of 8000 r / min. Dry the solution at 60 ° C for 12 h to obtain a cobalt ferrite-manganese ferrite / L-polylactic acid composite powder.

[0035] Step 3: Place the cobalt ferrite-manganese ferrite / levorotatory polylactic acid composite powder in a selective laser sintering system with a laser power of 1.8 W, a scanning speed of 150 mm / s, a scanning spacing of 0.2 mm, a spot diameter of 1 mm, a powder layer thickness of 0.1 mm, and a corresponding powder bed preheating temperature of 150 ° C. Sinter layer by layer according to the pre-established three-dimensional model. After sintering, remove the unsintered powder to obtain a cobalt ferrite-manganese ferrite / levorotatory polylactic acid composite antibacterial bone scaffold.

[0036] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A method for preparing a cobalt ferrite and manganese ferrite L-polylactic acid composite antibacterial bone scaffold, characterized in that: The following steps are involved: S1, preparing cobalt ferrite-manganese ferrite composite powder by in-situ growth of manganese ferrite on the surface of cobalt ferrite; S2, adding the prepared cobalt ferrite-manganese ferrite composite powder to ethanol to prepare a suspension, ultrasonically mixing the suspension with L-polylactic acid ethanol, and centrifugally drying to obtain a cobalt ferrite-manganese ferrite and L-polylactic acid composite powder; S3. Cobalt ferrite-manganese ferrite / L-polylactic acid composite antibacterial bone scaffold was prepared by selective laser sintering.

2. The method for preparing a cobalt ferrite and manganese ferrite left-handed polylactic acid composite antibacterial bone scaffold according to claim 1, characterized in that: In the step S1, a cobalt ferrite solution is prepared to obtain a cobalt ferrite-manganese ferrite / L-polylactic acid composite antibacterial bone scaffold, and the steps are as follows: S11, dispersing cobalt ferrite in ethanol and ultrasonically treating it to prepare an ethanol solution of cobalt ferrite; then in-situ growing manganese ferrite in the prepared cobalt ferrite solution, the steps are as follows: adding ferric acetylacetonate, manganese acetylacetonate, octadecyl alcohol, oleic acid, oleylamine, and phenyl ether to the prepared cobalt ferrite solution in sequence, ultrasonically dispersing and then magnetically stirring, heating the mixed solution in a tube furnace to react; repeatedly centrifuging and washing the solution with ethanol, and drying to obtain a cobalt ferrite-manganese ferrite composite powder; S12, dispersing L-polylactic acid powder in anhydrous ethanol to obtain a L-polylactic acid suspension, and then dispersing cobalt ferrite-manganese ferrite composite powder into the L-polylactic acid suspension to obtain a cobalt ferrite-manganese ferrite / L-polylactic acid composite suspension, and obtaining a cobalt ferrite-manganese ferrite / L-polylactic acid composite powder after ultrasonication, centrifugation, drying, and grinding; S13, placing the cobalt ferrite-manganese ferrite / L-polylactic acid composite powder in a selective laser sintering system, sintering it layer by layer according to a pre-established three-dimensional model, removing the unsintered powder after sintering, and obtaining the cobalt ferrite-manganese ferrite / L-polylactic acid composite antibacterial bone scaffold.

3. The method for preparing a cobalt ferrite and manganese ferrite left-handed polylactic acid composite antibacterial bone scaffold according to claim 2, characterized in that: In the step S11, the mass volume ratio of cobalt ferrite to ethanol is 1 mg:1 mL, the ultrasonic dispersion time is 30-60 min, and the temperature is 15-50°C; the magnetic stirring time is 30-60 min; the heating temperature is 300-350°C, and the heating rate is 10°C / min; the number of centrifugation is 2-4 times, the centrifugation time is 10-15 min, the centrifugation speed is 8000-10000 r / min, the drying time is 6-12 h, and the drying temperature is 50-80°C.

4. The method for preparing a cobalt ferrite and manganese ferrite L-polylactic acid composite antibacterial bone scaffold according to claim 2, characterized in that: In the step S12, the particle size of the L-polylactic acid is 10-40 um; in the cobalt ferrite-manganese ferrite / L-polylactic acid composite powder, the mass fraction of cobalt ferrite-manganese ferrite is 2-10%, and the mass fraction of the L-polylactic acid is 90-98%.

5. The method for preparing a cobalt ferrite and manganese ferrite L-polylactic acid composite antibacterial bone scaffold according to claim 2, characterized in that: In the step S13, during the laser sintering process, the laser power is 0.5-3W, the scanning speed is 100-200mm / s, the scanning spacing is 0.1-0.2mm, the spot diameter is 0.5-1.5mm, the powder layer thickness corresponding to the cobalt ferrite-manganese ferrite / levorotatory polylactic acid composite powder is 0.1mm, and the corresponding powder bed preheating temperature is 100-200°C.

6. The method for preparing a cobalt ferrite and manganese ferrite L-polylactic acid composite antibacterial bone scaffold according to claim 1, characterized in that: In the step S11, the particle size of the cobalt ferrite selected is 10-20 nm.

7. The method for preparing a cobalt ferrite and manganese ferrite L-polylactic acid composite antibacterial bone scaffold according to claim 2, characterized in that: In the step S11, the molar ratio of iron acetylacetonate to manganese acetylacetonate is 2:

1.

8. The method for preparing a cobalt ferrite and manganese ferrite L-polylactic acid composite antibacterial bone scaffold according to claim 2, characterized in that: In the step S11, the molar ratio of octadecyl alcohol, oleic acid and oleylamine is 5:6:

6.

9. The method for preparing a cobalt ferrite and manganese ferrite L-polylactic acid composite antibacterial bone scaffold according to claim 1, characterized in that: In the step S2, the synthesized cobalt ferrite-manganese ferrite composite powder has a core-shell structure, and the shell thickness is 0.5-2 nm.

Citation Information

Cited By

  • Composite scaffold material as well as preparation method and application thereof

    CN121371168A